Exploring Innovative Evaluation Strategies for Safety Education in Schools - Ojo, Oloyede Akinniyi; Quadri, Ganiyu Oluwaseyi; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2025)
This study explores innovative evaluation strategies for assessing the effectiveness of safety education programs in schools. Traditional methods of evaluation often rely on pre- and post-assessments or student surveys, which may fail to capture the broader impact of safety education on behavior, awareness, and long-term retention. This study examines alternate approaches to evaluation, including observational evaluations, peer assessments, digital portfolios, and real-time data-gathering technologies, such as mobile applications and gamified platforms. A descriptive design research methodology was used, using a mixed-methods approach that integrated qualitative data from interviews with educators and students with quantitative analysis derived from longitudinal surveys and behavioural monitoring. The results highlight the benefits of interactive and adaptive evaluation tools, which allow for continuous feedback and more personalised assessment of student engagement and learning outcomes. The research underscores the need to assess both information retention and the subsequent behavioural changes and mental reactions to safety instruction. The findings suggest that innovative, technology-enhanced evaluation strategies give an opportunity for extensive impact of safety programs, supporting the development of more effective and tailored educational interventions. The study contributes to the growing field of safety education by offering new perspectives on how to evaluate student learning in ways that foster deeper understanding and long-term safety awareness.